Psychological Disorder among Adolescent Students and its Intervention Strategies in Kenya- A Decade Review - Wangila , Caroline; Oseko , Agnes (African Journal of Education,Science and Technology (AJEST), 2022)
Globally, psychological disorder is a major challenge and in Kenya 1 out of 4 persons who seek healthcare in Kenya have a mental health condition. With all these damning statistics, the country is still struggling with providing affordable mental health care and treatment. Due to a growing interest in psychological disorder of adolescents in recent years and especially due to Covid-19 crisis, a review seems timely, to demonstrate the on psychological disorder among adolescent students in Kenya but also to identify proposed innervations measures that should be put in place to curb psychological issues among adolescent students in Kenya. This research looked through the databases of Google Scholar, Scopus, Web of Science, and ScienceDirect in search of articles that had been reviewed by experts and reported on the prevalence of psychological disorders among adolescents in Kenya. The scope of the search was narrowed to include just English-language articles that were published in the last ten years (2012 -2022). Results of the study indicated that the most prevalent psychological is depression and anxiety. Based on the findings of this study, additional research is required in Kenyan schools to understand the psychosocial risk factors for teenage depression in order to design therapeutic strategies. The Ministry of Education should establish effective interventions and strategies to combat psychological issues among adolescent students. Also, the ministry should implement proposed intervention strategies.